HOW DRONES ARE REVOLUTIONIZING PEST MANAGEMENT IN AGRICULTURE - Barão, Júlia Augusta; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2024)
Drones play a fundamental role in changes in the management of agricultural practices. With its great ability to efficiently monitor vast areas of land, it detects infestations early, allowing farmers to act quickly to mitigate crop damage. Furthermore, the use of drones enables the precise application of pesticides in affected areas, avoiding the rapid use of pesticides as well as the environmental impact. With the help of advanced data analysis, farmers achieve real planning control through strategic decisions. In short, drones are revolutionizing the management of agricultural practices, thus providing an efficient, sustainable and cost-effective approach to crop protection. The objective of this work is to compare the technical and economic efficiency of drones sprayed with agricultural tractors in soybean cultivation. The justification for this study is to provide a significant increase in this type of equipment in agriculture, as it avoids accumulation in the lines, in addition to a significant reduction in time and resources, reducing the environmental impact.